Improvements in radio-frequency transmission for ultra-high field magnetic resonance imaging through a bilateral monopole antenna. Issue 5 (4th July 2018) - Kim, Han-Joong; Heo, Phil; Han, Sang-Doc; Kim, Donghyuk; Song, Hyunwoo; Kim, Kyoung-Nam
ABSTRACT: Inhomogeneous magnetic flux density under ultra-high field (UHF) magnetic resonance imaging (MRI) is mainly caused by a shortened RF wavelength propagating through a dielectric medium. Numerous studies on several types of traveling-wave antenna for UHF MRI are underway because of the potential alternative strategy of a large field of view with deeper penetration depth. In this study, a bilateral monopole antenna is proposed to improve RF transmission field (| B 1 + |) uniformity at 297.2 MHz of 7 T. To investigate | B 1 + | uniformity in this scenario, a bilateral monopole antenna is optimized by performing an electromagnetic simulation using a finite-difference time-domain method and improvements achieved using the optimized bilateral monopole antenna structure are discussed.